Tetraploid Ancestry Provided Atlantic Salmon With Two Paralogue Functional T Cell Receptor Beta Regions Whereof One Is Completely Novel - Grimholt, Unni; Sundaram, Arvind Y. M.; Bøe, Cathrine Arnason; Dahle, Maria K.; Lukacs, Morten (Frontiers in Immunology, 2022)
Protective cellular immune responses have been difficult to study in fish, due to lack of basic understanding of their T cell populations, and tools to study them. Cellular immunity is thus mostly ignored in vaccination and infection studies compared to humoral responses. High throughput sequencing, as well as access to well assembled genomes, now advances studies of cellular responses. Here we have used such resources to describe organization of T cell receptor beta genes in Atlantic salmon. Salmonids experienced a unique whole genome duplication approximately 94 million years ago, which provided these species with many functional duplicate genes, where some duplicates have evolved new functions or sub-functions of the original gene copy. This is also the case for T cell receptor beta, where Atlantic salmon has retained two paralogue T cell receptor beta regions on chromosomes 01 and 09. Compared to catfish and zebrafish, the genomic organization in both regions is unique, each chromosomal region organized with dual variable- diversity- joining- constant genes in a head to head orientation. Sequence identity of the chromosomal constant sequences between TRB01 and TRB09 is suggestive of rapid diversification, with only 67 percent as opposed to the average 82-90 percent for other duplicated genes. Using virus challenged samples we find both regions expressing bona fide functional T cell receptor beta molecules. Adding the 292 variable T cell receptor alpha genes to the 100 variable TRB genes from 14 subgroups, Atlantic salmon has one of the most diverse T cell receptor alpha beta repertoire of any vertebrate studied so far. Perhaps salmonid cellular immunity is more advanced than we have imagined.